Analysis of technical efficiency among community-based seed producers in the savannas of Borno State, Nigeria - Amaza, P.S.; Udoh, E.J.; Abdoulaye, Tahirou; Kamara, A.Y. (2010)
The study examined the socio-economic characteristics of participating seed farmers in a community-based seed production scheme organized by the project, Promoting Sustainable Agriculture in Borno State (PROSAB). In addition, it determined the technical efficiency of resource use in PROSAB seed farms. Farm level survey data from 396 seed producers who cultivated maize, cowpea, soybean, rice, groundnut and sorghum were obtained using well structured questionnaires. The production parameters were estimated simultaneously with those of the models of inefficiency effects. Using the maximum likelihood estimation technique, asymptotic parameter estimates were evaluated to describe production inputs and efficiency determinants. Based on the results of gross margin analysis, the observed profit margins across the seed types conclusively revealed that every one naira spent in cultivating the seeds, some levels of financial benefits were derived as indicated by the output/input indices. Results further revealed that labour, farm size, seed and fertilizer were the most important inputs across the six crops. Inefficiency model analysis further revealed that the duration of the crop grown and ecological region predominantly affected the seed farm level of technical efficiency in input use. A mean technical efficiency of between 55% and 58% was identified, meaning that seed production under the scheme can still be increase by about 45% and 42% using available technology. The study recommends that, given the significance of seeds that have a shorter duration to maturity, quick maturing varieties of seeds should be promoted among farmers in the study area. Also, timely access to land augmenting input like fertilizer should be ensured.